Structural and functional analyses of copper-sensing operon regulator protein (CsoRGz) of Geobacillus zalihae strain T1 - Mangavelu, Ashwaani (2018)
Copper sensor regulator protein (CsoR) is widespread in most Gram positive bacteria. It is categorized under metalloregulatory protein that tightly regulates the passage of copper(I) ions to maintain cell viability, metabolism and preventing cell toxicity. Previously, gene annotation of a locally isolated Geobacillus zalihae strain revealed the presence of a CsoR-like hypothetical protein (CsoRGz) that shared only 30-38% sequence identity to structurally characterized CsoR proteins of various bacterial strains. This highlights the possibility of structural novelty of CsoRGz. As the actual 3D structure of CsoRGz is not available, information on possible novelty of its structure as well as its 3D copper(I) binding site and motif is unknown. This study aimed to elucidate the structure of CsoRGz via X-ray crystallography, identify the functional metal-binding residues and residues involved in dimerization of CsoRGz protein and compare its structure with other structurally characterized CsoR proteins. For this study, Escherichia coli BL21 Star Ⓡ (DE3) inserted with pET28b-CsoRGz vector was used to express the recombinant CsoRGz protein. CsoRGz protein was optimally expressed in LB medium at 37°C with IPTG induction at 0.1 mM and purified to homogeneity by affinity chromatography followed by gel filtration. The protein was stable when dialysed at pH 6.5 in the buffer containing 10 mM MES, 100 mM NaCl, 0.2 mM EDTA, 0.2 mM DTT and 5% glycerol. The purified CsoRGz protein was crystallized via sitting drop vapour diffusion method at 15 °C. Trigonal crystals corresponding to space group P3121 were grown in 5% (v/v) tacsimate TM (pH 7.0), 0.1 M HEPES (pH 7.0), 10% (w/v) polyethylene glycol monomethyl ether 5,000. The crystal was successfully diffracted at 1.83Å using an in-house X-ray beam with completeness of 100% with unit-cell parameters as follows; a=44.73, b=44.73, c=82.37 Å, where α=ß=90° and γ=120°. The Matthew’s coefficient analysis revealed that the crystal structure had one molecule per asymmetric unit with the solvent content of 32.82%. Its conserved copper-binding residues, Cys46-His71-Cys75, were found to be located at α2 helix onwards of the crystal structure similar to other CsoR proteins. The dimeric structure of CsoRGz was indicated using Protein, Interface and Structure and Assemblies (PISA) whereby the monomers were held together by disulphide bonds, hydrogen bonds and salt bridges and the residues involved in these respective interactions were duly mapped. CsoRGz showed largely similar global topology to other known Cu(I) bound CsoRs with minimal differences in the characteristics of the Cu(I) binding pocket whereby CsoRGz had a more hydrophobic environment than other reported CsoRs.